UPAYA STOP ASIAN AMERICANS PACIFIC ISLAND HATE DALAM MENANGANI ISU GLOBAL TERKAIT RASISME DI AMERIKA SERIKAT PADA FORUM PBB - Tia Rachmi; Irwan Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The spread of Covid-19 has an impact on increasing anti-Asian racism globally, especially in the United States. There have been 10,370 reports of incidents of racism and attacks against Asians and their descendants in the United States since March 2020. The rapidly growing crisis of anti-Asian racism in the United States prompted the formation of an organization called Stop Asian-Americans and Pacific Islanders Hate (Stop AAPI Hate) which seeks to take the issue to a global level to stop anti-Asian racism in the United States. The author examines how Stop AAPI Hate's efforts deal with global issues related to racism in the United States at the United Nations Forum. The author uses a qualitative method with a case study approach. The data comes from the experiences of victims who are registered as experiencing acts of racism at Stop AAPI Hate, data from organizations concerned that have collaborated in handling racism in the United States, articles, journals, books and other official websites related to the role or actions of Stop AAPI Hate. This study uses the perspective of Pluralism with the theory of the Role of Non-Governmental Organizations at the level of analysis of non-governmental organizations. The results of the study show several steps as a form of Stop AAPI Hate's efforts in dealing with global issues related to racism in the United States at the United Nations forum, including data and research, changing narratives, advocacy and community support to raise the issue of anti-Asian racism to a global level and get support from other international actors in dealing with the issue of anti-Asian racism in the United States post-Covid-19 at the UN forum. Keywords: Stop AAPI Hate, Anti-Asia, United Nations, Racism, Covid-19